2018
DOI: 10.3148/cjdpr-2018-011
|View full text |Cite
|
Sign up to set email alerts
|

Parental Reports of Lunch-Packing Behaviours Lack Accuracy: Reported Barriers and Facilitators to Packing School Lunches

Abstract: Strategies to improve packed lunches should move beyond parental nutrition knowledge and importance of lunch packing to address parental barriers and facilitators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 24 publications
0
23
0
Order By: Relevance
“…25 Although parents value the importance of packing a healthy school lunch for their children, it is evident parents do not have total control over what is included, as children substantially influence the school lunch food selection and packing process. 15,19,22 Unfortunately, the barriers parents encounter may supersede parental attitudes and hinder the translation of their healthy values into behaviors. 22 Our review identified several barriers that parents encounter when packing healthy food for their children-most prominently the school environment, children's influence, cost, and convenience.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…25 Although parents value the importance of packing a healthy school lunch for their children, it is evident parents do not have total control over what is included, as children substantially influence the school lunch food selection and packing process. 15,19,22 Unfortunately, the barriers parents encounter may supersede parental attitudes and hinder the translation of their healthy values into behaviors. 22 Our review identified several barriers that parents encounter when packing healthy food for their children-most prominently the school environment, children's influence, cost, and convenience.…”
Section: Discussionmentioning
confidence: 99%
“…15,20,21 Furthermore, parents reported receiving requests from their children to alter the lunchbox contents, 21 decrease portion sizes, 19 and exclude fruit 19 so children could eat quickly and go out to play. School food regulations such as allergy policies and healthy eating rules influenced parental lunchpacking decisions [20][21][22][23] ; however, many parents felt that ultimately the decision to pack certain foods was their own, and routinely defied school food rules. 20,21,23 Lastly, food safety concerns prevented parents from putting healthier items into the lunchbox 19,22 as parents preferred to pack pre-packaged, temperature stable foods because refrigeration was not available to students.…”
Section: School Environmentmentioning
confidence: 99%
See 3 more Smart Citations